2009
DOI: 10.1007/s10336-009-0396-0
|View full text |Cite
|
Sign up to set email alerts
|

Compared distribution within a disturbed fishpond ecosystem of breeding ducks and bird species indicators of habitat quality

Abstract: The distribution of breeding ducks versus three other bird species (Mute Swan Cygnus olor, Black-headed Gull Larus ridibundus and Purple Heron Ardea purpurea) among waterbodies was investigated in the Dombes area, Eastern France, where breeding duck populations have undergone a severe decline following a large-scale transformation of meadow habitat into cropland. Higher Pochard Aythya ferina, Tufted Duck Aythya fuligula, Redcrested Pochard Netta rufina and Gadwall Anas strepera pair densities were recorded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Stable brood: pair ratio in Forez contrasted with a decrease recorded in Dombes and in Brenne, which could correspond either to a lower proportion of adults actually nesting, or to higher losses before or immediately after hatching. Such a negative trend could be hypothetically related to the arrival and the expansion of the Coypu, with correlative impacts on helophyte stands and reduction in available areas of nesting habitat (Curtet et al, 2008), thereby increasing the risk of clutch predation (Broyer, 2009). Under that hypothesis however, it would be difficult to explain the absence of negative effect on the brood: pair ratio in Forez despite the increased density of recorded pairs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Stable brood: pair ratio in Forez contrasted with a decrease recorded in Dombes and in Brenne, which could correspond either to a lower proportion of adults actually nesting, or to higher losses before or immediately after hatching. Such a negative trend could be hypothetically related to the arrival and the expansion of the Coypu, with correlative impacts on helophyte stands and reduction in available areas of nesting habitat (Curtet et al, 2008), thereby increasing the risk of clutch predation (Broyer, 2009). Under that hypothesis however, it would be difficult to explain the absence of negative effect on the brood: pair ratio in Forez despite the increased density of recorded pairs.…”
Section: Discussionmentioning
confidence: 77%
“…In each region, pond surroundings are made up mainly by croplands or grasslands, more intensively managed in Dombes where a massive conversion of grasslands to cereal crops since the 1970s had severely affected duck breeding conditions (Tournier, 1990;Broyer, 2000). This reduction in meadow habitats in Dombes may have led to nest concentration in aquatic vegetation and increased impacts of nest predators (Broyer, 2009). The game harvest at the opening of the hunting season probably impinges on local production.…”
Section: > Study Regionsmentioning
confidence: 99%
“…For example, the abundance of gulls ( Larus spp.) was correlated with better waterbird brood success, probably because gulls provided defense against predators (Arzel et al, 2015 ; but see Broyer ( 2009 ) where no such effect of gulls was found). However, facilitative interactions will not occur in all species pairings and some interactions will have a negative impact on habitat quality for one species, such as aggression by Mute Swans ( Cygnus olor ) leading to a reduction in breeding pair density of Mallards ( Anas platyrhynchos ; Broyer, 2009 ).…”
Section: Synthesis Of Reviewed Studiesmentioning
confidence: 99%
“…There were also 4 species in the forest of Bukit Lesung, namely Lophopetalum javanicum, Syzygium racemosum, Dysoxylum nutans and Dendrocnide peltata Table 4. Indicator species has been used in many ecological research, however mostly these are in a form of animal species or microorganism, moreover these indicators usually refers to a species in degraded or disturbed habitat (Bachand et al 2014;Broyer 2009;Newton and Horner 2003). Plant species can also be used as indicators.…”
Section: Indicator Speciesmentioning
confidence: 99%